Homeostatic Control of Hpo/MST Kinase Activity through Autophosphorylation-Dependent Recruitment of the STRIPAK PP2A Phosphatase Complex. - Zheng, Y.; Liu, B.; Wang, L.; Lei, H.; Pulgar Prieto, K.D.; Pan, D. (Cell reports, 2017)
The Hippo pathway controls organ size and tissue homeostasis through a kinase cascade leading from the Ste20-like kinase Hpo (MST1/2 in mammals) to the transcriptional coactivator Yki (YAP/TAZ in mammals). Whereas previous studies have uncovered positive and negative regulators of Hpo/MST, how they are integrated to maintain signaling homeostasis remains poorly understood. Here, we identify a self-restricting mechanism whereby autophosphorylation of an unstructured linker in Hpo/MST creates docking sites for the STRIPAK PP2A phosphatase complex to inactivate Hpo/MST. Mutation of the phospho-dependent docking sites in Hpo/MST or deletion of Slmap, the STRIPAK subunit recognizing these docking sites, results in constitutive activation of Hpo/MST in both Drosophila and mammalian cells. In contrast, autophosphorylation of the Hpo/MST linker at distinct sites is known to recruit Mats/MOB1 to facilitate Hippo signaling. Thus, multisite autophosphorylation of Hpo/MST linker provides an evolutionarily conserved built-in molecular platform to maintain signaling homeostasis by coupling antagonistic signaling activities.